An improved particle swarm optimization (PSO) based MPPT for PV With reduced steady-state oscillation - Ishaque, K.; Salam, Z.; Amjad, M.; Mekhilef, Saad (Institute of Electrical and Electronics Engineers, 2012)
This paper proposes an improved maximum power point tracking (MPPT) method for the photovoltaic (PV) system using a modified particle swarm optimization (PSO) algorithm. The main advantage of the method is the reduction of the steadystate oscillation (to practically zero) once the maximum power point (MPP) is located. Furthermore, the proposedmethod has the ability to track the MPP for the extreme environmental condition, e.g., large fluctuations of insolation and partial shading condition. The algorithm is simple and can be computed very rapidly; thus, its implementation using a low-cost microcontroller is possible. To evaluate the effectiveness of the proposed method, MATLAB simulations are carried out under very challenging conditions, namely step changes in irradiance, step changes in load, and partial shading of the PV array. Its performance is compared with the conventional Hill Climbing (HC) method. Finally, an experimental rig that comprises of a buckâboost converter fed by a custom-designed solar array simulator is set up to emulate the simulation. The software development is carried out in the Dspace 1104 environment using a TMS320F240 digital signal processor. The superiority of the proposed method over the HC in terms of tracking speed and steady-state oscillations is highlighted by simulation and experimental results.